The Wall Street journal guide to information graphics : the dos and don'ts of presenting data, facts, and figures - Wong, Dona M.
The definitive guide to the graphic presentation of information contains a step-by-step guide to executing clear, concise, and intelligent graphics. The most current digital information is included along with practical advice, making this an essential reference.